External Debt And Growth : A Panel Analysis Of Asian Countries - Kon, Thian Ling (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This research seeks to examme the nexus between external debt and economic growth in Asian countries under the linear estimation of panel error correction model. The analysis adopted two different panel data sets of seventeen and twelve Asian countries over the periods of 1988-2006 and 1981-2006 respectively as a mean to test the consistency of the result under two different estimations. The presented results in panel-17 suggest that there is an absence of long-run causality linkage between external debt and GDP. However, unidirectional relationship has found to be established from ED to GDP in the short-run. This results is however does not reinforce by the estimation under panel-12. The existence of the relationship between GDP and EXP indicates that Asian countries have supported the export-led growth strategy in which the extent of economic growth does not fully determine by external debt level among these countries.